2020
DOI: 10.1055/a-1081-1635
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Blood Pressure Rise after Treatment with Anti-vascular Endothelial Growth Factor Agents

Abstract: Background It has previously been shown that the process of anti-vascular endothelial growth factor (VEGF) injections can lead to a significant increase of blood pressure. The aim of this study was to investigate whether this blood pressure increase was reproducible with repeated anti-VEGF injections. Patients and Methods Patients with a systolic blood pressure of ≥ 180 mmHg during previous injections who were scheduled for further injections were asked to participate in this study. Systolic as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previously, Berger et al 17 have demonstrated that SBP may rise by 18 ± 15 mmHg at the time of IVI. Wyssmüller et al 18 also found that SBP rose from 157.3 ± 5.9 mmHg to 175 ± 6.7 mmHg at the time of the injection. Our study found that an SBP rise of ⩾10 and ⩾20 mmHg was seen in 83.8% and 69.5% of patients.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, Berger et al 17 have demonstrated that SBP may rise by 18 ± 15 mmHg at the time of IVI. Wyssmüller et al 18 also found that SBP rose from 157.3 ± 5.9 mmHg to 175 ± 6.7 mmHg at the time of the injection. Our study found that an SBP rise of ⩾10 and ⩾20 mmHg was seen in 83.8% and 69.5% of patients.…”
Section: Discussionmentioning
confidence: 86%